2003
DOI: 10.1124/jpet.103.056622
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Glutathione Depletion Is a Mechanism Responsible for the Anti-Inflammatory Effects of Ethyl Pyruvate in Cultured Lipopolysaccharide-Stimulated RAW 264.7 Cells

Abstract: Ethyl pyruvate (EP), an effective scavenger of reactive oxygen species, is also an anti-inflammatory agent in a variety of in vivo and in vitro model systems. To gain a better understanding of the molecular basis for the anti-inflammatory effects of EP, we compared the pharmacological properties of EP and N-acetyl-L-cysteine (NAC), a well studied scavenger of reactive oxygen species and a precursor for the endogenous antioxidant glutathione (GSH). The studies were performed using RAW 264.7 murine macrophage-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
82
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 62 publications
9
82
0
Order By: Relevance
“…Results from in vivo and in vitro studies support the view that ethyl pyruvate inhibits NF-B DNA binding (Yang et al, , 2003(Yang et al, , 2004Uchiyama et al, 2003;Han et al, 2004;Song et al, 2004). Moreover, Song et al (2004) recently reported data suggesting that ethyl pyruvate might react with the sulfhydryl-containing compound, glutathione.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Results from in vivo and in vitro studies support the view that ethyl pyruvate inhibits NF-B DNA binding (Yang et al, , 2003(Yang et al, , 2004Uchiyama et al, 2003;Han et al, 2004;Song et al, 2004). Moreover, Song et al (2004) recently reported data suggesting that ethyl pyruvate might react with the sulfhydryl-containing compound, glutathione.…”
supporting
confidence: 61%
“…In many of these models of acute critical illness, treatment with ethyl pyruvate down-regulates the expression of various pro-inflammatory genes, including inducible nitric oxide synthase (iNOS), tumor necrosis factor, cyclooxygenase-2, and interleukin (IL)-6 (Yang et al, , 2003(Yang et al, , 2004Uchiyama et al, 2003). Similarly, ethyl pyruvate inhibits IL-6 and iNOS expression, nitric oxide production, and/or secretion of the pro-inflammatory protein HGMB1 by immunostimulated Caco-2 human enterocytelike cells or lipopolysaccharide-stimulated RAW 264.7 murine macrophage-like cells (Ulloa et al, 2002;Sappington et al, 2003a,b;Song et al, 2004). These latter findings support the view that ethyl pyruvate has activity as an anti-inflammatory agent; however, the molecular mechanisms underlying the anti-inflammatory effects of ethyl pyruvate remain to be elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that 20 mM NAC downregulates basal NF-kB DNA binding in RAW 264.7 macrophages and also inhibits LPS-stimulated NF-kB DNA binding in these cells (54). In contrast, few studies indicate that NAC fails to inhibit LPS-induced activation of NF-kB in RAW 264.7 macrophages (55); yet in other studies, NAC has been shown to inhibit activation of NF-kB in alveolar macrophages induced by TNF-a (56).…”
Section: Discussionmentioning
confidence: 99%
“…The serum was collected and stored frozen at -80 °C until assayed for IL-6 and IL-10 using ELISA kits from R&D Systems (Minneapolis, MN, USA) according to the manufacturer's instructions. Serum nitrite concentration was measured using the Greiss reaction, as described (32).…”
Section: Measurement Of Il-6 Il-10 and Nitrite Concentrations In Serummentioning
confidence: 99%